2004
DOI: 10.1145/1028523.1028550
|View full text |Cite
|
Sign up to set email alerts
|

Animation of reactive gaseous fluids through chemical kinetics

Abstract: Although chemically reactive fluids may be used effectively to increase the reality of visual effects, little work has been done with the general modeling of chemical reactions in computer animation. In this paper, we attempt to extend an established, physically based fluid simulation technique to handle reactive gaseous fluids. The proposed technique exploits the theory of chemical kinetics to account for a variety of chemical reactions that are frequently found in everyday life. In extending the existing flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Each component di of D represents the volume ratio of fluid i, and the sum of all components in one vector equals one. This representation is similar to the volume of fluid method [Kang et al 2010;Ihm et al 2004] used in multiple fluid simulation. D values are advected in the system on both the global network and local regions.…”
Section: Materials Transportationmentioning
confidence: 99%
“…Each component di of D represents the volume ratio of fluid i, and the sum of all components in one vector equals one. This representation is similar to the volume of fluid method [Kang et al 2010;Ihm et al 2004] used in multiple fluid simulation. D values are advected in the system on both the global network and local regions.…”
Section: Materials Transportationmentioning
confidence: 99%
“…Chemical reaction phenomena, like fire and flame, explosion, and catalysis, are abundant in the real world, and are important elements that are routinely generated in the special effects industry. In order to reproduce such reactive fluids, Ihm et al 15 explored the theory of chemical kinetics for effectively simulating reactive gases containing multiple reacting species. While generated several interesting fluid effects of reacting gases, the method often required a substantial demand for memory space, especially when a complex reaction mechanism involving many chemical species was simulated.…”
Section: Related Workmentioning
confidence: 99%
“…Iham et al [8] showed that by coupling reaction effects to the velocity field, explosion effects can be simulated. Unlike our work, their focus was on explosions, not pattern formation.…”
Section: Previous Workmentioning
confidence: 99%